Fledgling Psychopathic Features and Pathological Delinquency: New Evidence - DeLisi, Matt (American journal of criminal justice, 2014)
Fledgling psychopathy is a construct that has proven useful in organizing the nomological network of conduct problems and psychopathology in children and adolescents. Drawing on data from an institutionalized sample of delinquents ( n = 252), the current study compared ADHD, CD, and ADHD+CD youth on psychopathic personality features and their association with pathological delinquency. Youths with ADHD+CD were significantly more psychopathic than their peers. Although callousness, unemotionality, and remorselessness are generally theorized to define the fledgling psychopathic youth, ROC-AUC models found that thrillseeking and impulsiveness were the strongest classification variables for delinquency and violent delinquency at the 90th percentiles. Implications for research and practice with antisocial youth are proffered.